1962
DOI: 10.1139/m62-057
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES OF MARINE PLANKTONIC DIATOMS:II. USE OF CYCLOTELLA NANA HUSTEDT FOR ASSAYS OF VITAMIN B12 IN SEA WATER

Abstract: Cyclo~ella na?zn I-Iustedt, a small centric diatom requiring vitamin Blr, was tested as a potential assay organism for that vitamin. Dose-respo~lse curves, measured by optical density and cell count, showed a linear relation between gro\vth and BIZ concel~tration between 0 and a t least 2 kkg/rnl of the vitamin. Sincc the diatom is hardy, grows rapidly under a variety of conditions, and Inay be preserved for later esaminatio~l, it represents a ~~s e f u l assay organism for certain applications such as ocearlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Vitamin B 12 was assayed with the marine diatom CycZoteZZu nuna Husted,t Strain 3H which is sensitive in the range of 0-2 pg B12/ml (Ryther and Guillard 1962 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin B 12 was assayed with the marine diatom CycZoteZZu nuna Husted,t Strain 3H which is sensitive in the range of 0-2 pg B12/ml (Ryther and Guillard 1962 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Early studies suggested a strong correlation between vitamin depletion in seawater and diatom bloom termination (129,130). Cobalamin, or vitamin B 12 , is by far the most studied vitamin in relation to diatom requirements (32,50,152). Cobalamin is required in organisms lacking the cobalamin-independent methionine synthase, MetE.…”
Section: Synergistic Interactionsmentioning
confidence: 99%
“…One of the most common interactions is the bacterial release of growth promoting factors such as vitamins that are needed by microalgae (e.g. cobalamin, thiamine and biotin) (Carlucci and Silberna, 1969;Croft et al, 2005;Haines and Guillard, 1974;Kazamia et al, 2012;Ryther and Guillard, 1962;Tang et al, 2010). By their role in the nitrogen cycle, bacteria (e.g.…”
Section: Introductionmentioning
confidence: 99%